Correction to: Attenuated self-serving bias in people with internet gaming disorder is related to altered neural activity in subcortical-cortical midline structures - Yifan Wang; Li Zheng; Chenggong Wang; Xiuyan Guo (BMC Psychiatry, 2020)
An amendment to this paper has been published and can be accessed via the original article.